Work Performance Assessed through Job Motivation and Teamwork Moderated by the Utilization of Information Technology at Widya Trans Cargo Employees in Jakarta - Agni Setiawan; Zandra Dwanita Widodo; Mrihrahayu Rumaningsih (International Journal of Business and Applied Economics, 2023)
The aims of this research were 1) to examine and measure the influence of work motivation on work achievement in employees. (2) To test and measure the effect of team work on work performance in employees. (3) To find out whether the use of information technology as a moderating variable weakens or strengthens the effect of work motivation on work achievement for employees. (4) To find out whether the use of information technology as a moderating variable weakens or strengthens the effect of teamwork on work achievement for Widya Trans Cargo employees. This research was conducted on employees of PT. Widya Trans Cargo Jakarta. The population in this study were all employees at Widya Trans Cargo consisting of central employees and branch employees, namely 78 employees. The entire population in this study, totaling 78 employees, were all taken as samples, with saturated sample sampling. The results of the study found that motivation and teamwork had a significant positive effect on the work performance of Widya Trans Cargo Jakarta employees. Utilization of information technology strengthens the influence of work motivation and teamwork on employee performance.